The species of Eupelmus (Eupelmus) Dalman and Eupelmus (Episolindelia) Girault (Hymenoptera: Eupelmidae) in North America north of Mexico - Gibson, Gary A. P. (Zootaxa, 2011)
The species of Eupelmus (Eupelmus) Dalman and Eupelmus (Episolindelia) Girault (Chalcidoidea: Eupelmidae) in North America north of Mexico are revised. Illustrated keys are given to differentiate the three subgenera of Eupelmus and females and known males of 19 recognized species of E. (Eupelmus) and E. (Episolindelia). Five species are classified in E. (Episolindelia), including the three newly described species E. (Episolindelia) fuscipectus n. sp., E. (Episolindelia) grisselli n. sp., and E. (Episolindelia) varicauda n. sp., which are based only on females. Eupelmus rubicola (Ashmead), described originally from a unique male, is tentatively associated with females and is classified as E. (Episolindelia) rubicola n. stat. based on this association. Fourteen species are classified in E. (Eupelmus), including the four newly described species E. (Eupelmus) arizonensis n. sp., E. (Eupelmus) curticinctus n. sp., E. (Eupelmus) nitifrons n. sp., and E. (Eupelmus) pervius n. sp. Two Palaearctic species, E. (Eupelmus) stramineipes Nikol’skaya and E. (Eupelmus) microzonus Förster, are newly recorded from North America. Newly placed in synonymy under E. microzonus is E. (Eupelmus) insulae Masi n. syn. It is further suggested that E. (Eupelmus) nigricauda Nikol’skaya likely is also a junior synonym of E. microzonus. Information is also given on the identity of the Palaearctic names E. (Eupelmus) afer Silvestri, E. (Eupel- mus) martellii Masi, E. (Eupelmus) nubilipennis Förster, E. (Eupelmus) spongipartus Förster, and E. (Eupelmus) urozonus Dalman. A lectotype is designated for E. (Eupelmus) pini Taylor and under this name are placed in synonymy the Palaearctic names E. aloysii Russo n. syn., E. carinifrons Yang n. syn., E. sculpturatus Nikol’skaya n. syn., and Eupelmus suecicus Hedqvist n. syn. Four other new synonyms made are Eupelmus amicus Girault under E. (Eupelmus) cushmani(Crawford) n. syn., Eupelmus ficigerae (Ashmead) under E. (Eupelmus) dryorhizoxeni Ashmead n. syn., Eupelmus momphae Gahan under E. (Eupelmus) cyaniceps Ashmead n. syn., and Eupelmus quercus under E. (Eupelmus) cynipidis Ashmead n. syn. The subspecies Eupelmus cyaniceps scolyti Liao, described originally from China, is treated as E. (Eupelmus) scolyti Liao n. stat. and compared to E. (Eupelmus) formosae Ashmead. Eupelmus floridanus Howard is treated as a nomen dubium and the following 20 species are newly transferred from Eupelmus to other genera — Anastatus (Anastatus) ashmeadi (Melander & Brues) n. comb., Brasema aurata (Ashmead) n. comb., Brasema barda (Girault) n. comb., Brasema brevicauda (Crawford) n. comb., Brasema bruchivora (Crawford) n. comb., Brasema coccidis (Girault) n. comb., Brasema dryophantae (Ashmead) n. comb., Brasema flavovariegata (Ashmead) n. comb., Brasema fonteia (Walker) n. comb., Brasema juglandis (Ashmead) n. comb., Brasema lamachus (Walker) n. comb., Brasema limneriae (Howard) n. comb., Brasema macrocarpae (Ashmead) n. comb., Brasema neococcidis (Peck) n. comb., Brasema neomexicana (Girault) n. comb., Brasema rosae (Ashmead) n. comb., Brasema speciosa (Girault) n. comb., Brasema sphaericephalus (Ashmead) n. comb., Reikosiella (Reikosiella) biguttata (Girault) n. comb., and R. (Reikosiel- la) charitopoides (Girault) n. comb.